Pengembangan dan Implementasi Program SPEDE KPSP Berbasis Web untuk Meningkatkan Kompetensi Guru PAUD dalam Deteksi Dini Perkembangan Anak: Indonesia - Lestari, Nur Eni; Susaldi, Susaldi; Mulachela, Zainab Husin; Cahyati, Arinda Rizki; Azalia, Devia Rahma (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Early Childhood Education (ECE) represents a crucial stage in establishing the foundation for children’s overall development. However, many ECE teachers continue to face challenges in the early detection of developmental delays. A real example can be found at TEKAKU Pre-School Cinere, Depok, where teachers were not yet accustomed to using standardized developmental screening tools, resulting in inaccurate developmental monitoring outcomes. To address this issue, the SPEDE KPSP Program (Skrining Perkembangan Efektif dan Efisien menggunakan Kuesioner Pra Skrining Perkembangan, Effective and Efficient Developmental Screening using the Developmental Pre-Screening Questionnaire) was developed to enhance the competence of ECE teachers. The implementation process was carried out through five main phases: (1) socialization, (2) training, (3) technology implementation through a web-based digital application (benihbahagia.co.id), (4) mentoring and evaluation, and (5) program sustainability. The results indicated that the educational interventions significantly improved participants’ understanding of child development and the importance of early detection (p = 0.021; p < 0.05). Training sessions were also effective in enhancing teachers’ screening skills (p = 0.002; p < 0.05). The benihbahagia.co.id web application supported the process by facilitating KPSP administration, data storage, result visualization, and follow-up recommendations. Its key features include child data management, developmental visualization, automatic recommendations, educational materials, downloadable reports, and red-flag alerts. Mentoring activities confirmed that the platform was practical and user-friendly, enabling teachers to perform developmental screening efficiently. The program demonstrates potential for wider adoption in other ECE institutions, thereby strengthening early detection systems and expanding the network of competent and digitally literate ECE teachers. Keywords: Competence, Development, Early Childhood Education (ECE), KPSP, Teacher